Economic Law and Standardization: A Basis for Avoiding Risks in Business - Popovych, Tetiana G.; Bezukh, Oleksandr V.; Trofanchuk, Hryhoriy I.; Pozhodzhuk, Tetiana B. (International Journal of Criminology and Sociology, 2021)
Currently, in Ukraine, there is a system of technical regulation as part of the general system of standardization. Technical regulation is defined as a means of state regulation, which, like any legal regulation, is implemented by appropriate legal means. This explains the relevance of this study. This paper investigates the Economic Code of Ukraine, several Ukrainian laws (the Law of Ukraine "On Environmental Audit", the Law of Ukraine "On Standardization", the Law of Ukraine "On Technical Regulations and Conformity Assessment", etc.), and State standards. Technical regulation was also considered as a general category and a legal phenomenon, as a result of which it was noted that the technical regulation adopted in Ukraine for dividing products into food and non-food products is only a matter of supervision over the conformity of goods and the use of conditions for a specific legal act and type of product. It was concluded that standardization proceeds from social regulation and generates norms of a technical, organizational, or other orderly nature, transforming into legal provisions. Therewith, technical regulation also derives from legal regulation and gives rise to technical guidelines, which constitute statutory regulations that form part of the national legislation of Ukraine, including economic legislation. As a result, it is proposed to improve and supplement the wording of Part 2 Article 16 of the Law of Ukraine "On Standardization", and it is also proposed to reword Article 24 of the Law of Ukraine "On Technical Regulations and Conformity Assessment". Keywords: Technical regulation, laws of Ukraine, state standards, ISO, regulations.